Acoustic feedback cancellation for a multi-microphone earpiece based on a null-steering beamformer - Schepker, H.; Tran, Linh T.T.; Nordholm, Sven; Doclo, S. (2016)
In order to reduce acoustic feedback in hearing aids, adaptive filters are commonly used to estimate the feedback contribution in the microphone(s). While theoretically allowing for perfect feedback cancellation, in practice the solution is typically biased due to the closed-loop acoustical system. In this paper, we propose to use a fixed beamformer to cancel the acoustic feedback for an earpiece with multiple integrated microphones and loudspeakers. By steering a spatial null in the direction of the hearing aid loudspeaker we show that theoretically perfect feedback cancellation can be achieved. Experimental results using measured acoustic feedback paths from an earpiece with two microphones in the vent and a third microphone in the concha show that the proposed fixed beamformer provides a reduction of the acoustic feedback and substantially increases the added stable gain while maintaining a high perceptual speech quality even for unknown acoustic feedback paths, e.g., after repositioning of the earpiece or with a telephone receiver close to the ear.